2016
DOI: 10.1177/2047487316679526
|View full text |Cite
|
Sign up to set email alerts
|

Adult derived genetic blood pressure scores and blood pressure measured in different body postures in young children

Abstract: Aims Several genes are related to blood pressure (BP) levels in adults, but it is largely unknown whether these genes also determine BP early in life. Methods Systolic BP (SBP) and diastolic BP (DBP) were measured in 720 5-year-old children from the WHeezing-Illnesses-STudy-LEidsche-Rijn (WHISTLER) birth cohort in sitting and supine positions using a semi-automatic oscillometric device. Illumina chip technology was used to genotype 18, 19, 11 and 12 single nucleotide polymorphisms associated with adult SBP, DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Potentially, genetic factors play a role as genetic variations associated with raised systolic BP in adulthood also predict systolic BP levels in children. 42 Based on pathophysiological differences that are associated with either low or high central systolic BP, ISH of the young is likely associated with both low CVD risk and ‘true’ ISH with raised CVD risk. Estimation of central systolic BP may offer the potential to discriminate subjects with ISH who have low central BP and CVD risk from those who have high central blood pressure and increased risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, genetic factors play a role as genetic variations associated with raised systolic BP in adulthood also predict systolic BP levels in children. 42 Based on pathophysiological differences that are associated with either low or high central systolic BP, ISH of the young is likely associated with both low CVD risk and ‘true’ ISH with raised CVD risk. Estimation of central systolic BP may offer the potential to discriminate subjects with ISH who have low central BP and CVD risk from those who have high central blood pressure and increased risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on newer aspects of HT in children, such as the relation to adult-derived genetic BP scores, prenatal exposure to maternal stress, and the effect of traffic-related air pollution, are also being reported. [17][18][19] Highly significant associations (p < 0.0001) found in our univariate analysis are likely related to the large sample size of this study. A significant variation of the prevalence of HT between different geographical locations was observed.…”
Section: Discussionmentioning
confidence: 65%
“…Scenario a) could be caused by changes of lifestyle, such as an increased prevalence of obesity, or genetic background, which may vary locally. 3,6 The influence of genetics on BP values in children has recently been studied: Jansen et al demonstrated an association between higher systolic BP with a higher genetic risk score, but only when BP was measured in a supine but not a sitting position. 6 As a reason for this, they postulated that sitting BP is more influenced by factors such as body size, thus rather reflecting lifestyle, whereas supine BP might better reflect innate BP values predominantly driven by genes.…”
mentioning
confidence: 99%
“…3,6 The influence of genetics on BP values in children has recently been studied: Jansen et al demonstrated an association between higher systolic BP with a higher genetic risk score, but only when BP was measured in a supine but not a sitting position. 6 As a reason for this, they postulated that sitting BP is more influenced by factors such as body size, thus rather reflecting lifestyle, whereas supine BP might better reflect innate BP values predominantly driven by genes. 6 As Narang et al measured BP in a sitting position, their result, if indicating a true increase in AHT prevalence, probably reflects lifestyle rather than genetics.…”
mentioning
confidence: 99%
See 1 more Smart Citation